Treatment of COVID-19 in peru and bolivia, and self-medication risks - Román, Brenda Rojas (2020)
Introduction: Various drugs are being used against the symptoms caused by COVID-19, without being approved for these purposes. Many of these drugs have small safety margin and very risky adverse effects on health, a reason why they require prescription and, above all, medical monitoring and follow-up. Unfortunately, there are many cases of self-medication in Peru and Bolivia that require prompt management. Objective: To carry out a systematic review of the scientific literature that presents evidence about the effectiveness and adverse reactions of the drugs currently used against COVID-19 in Peru and Bolivia. Methods: Qualitative research based on the systematic review of the scientific literature available in PubMed, as well as in the national regulations of Peru and Bolivia related to the etiology, epidemiology, symptoms, as well as treatments approved and discontinued by both countries since the exacerbation of the COVID-19 crisis and the completion of clinical studies to date. Conclusions: The drugs used in Peru and Bolivia for treating COVID-19 have side effects and possible risks to the health of people who unfortunately self-medicate. Greater control of these drugs is required to avoid their free acquisition, and to improve the national and regional strategy to evaluate the possible symptomatic treatments of COVID-19, taking into consideration the high probability of survival of the disease and the risk posed by using these drugs, which, in the future, could cause serious adverse effects on public health in the two countries.